A Study on Using Phonics Method in TeachingPpronunciation to the Beginners of English at Tienganh123 English Center = Nghiên cứu về sử dụng phương pháp ghép vần trong việc dạy phát âm cho người mới bắt đầu học Tiếng Anh tại trung tâm Tiếng Anh 123. M.A Th - Lương, Thị Hoài Phương (University of Languages and International Studies, 2017)
The purpose of this study is to explore whether using phonics to teachpronunciationcan help English beginners better at pronunciation. It has two foci. One is to investigate whether phonics method can help English better in pronunciation or not. The other is to identify the situation when the phonics instruction is implemented in the classroom.This study employed a qualitative and quantitative approach in which it primarily relied on the use of action research. Eighteenstudents from English123 center participated in the study. The findings of the current study revealed that phonics instruction has positive effect on English beginners in leaning pronunciation; however, it is still problematic. Even though Phonics could help students pronounce consonant well, most of students feel confused with pronouncing the vowels and diphthongs. The reason is that there are too many spelling rules for each sound to remember.